ANALISIS GAYA BAHASA KIASAN DALAM BERITA INDUSTRI PADA MEDIA DIGITAL REPUBLIKA DAN MEDIA INDONESIA - Rizaldi Sardani (Universitas Putera Batam, 2018)
Figurative languages are often found in everyday life, one of which is in the industry news. This study aims to know and understand the purpose of the use of figurative language style used in the news industry in the mass media. This research is a descriptive qualitative research by applying observation method and record technique. The results showed that 25 pieces of industry news data contained 15 pieces of metaphors, 8 pieces of personification, 1 piece hyperbola and 1 piece synecdoche. In general, it can be concluded that metaphor is the most commonly used in industry news.